Adnyamathanha Archives and Colonial Ruins: The UNSETTLED Project. Issue 2 (3rd April 2019) - Cooke, Grayson; Morgain, Dea
ABSTRACT: The exhibition UNSETTLED: Colonial Ruin in the Flinders Ranges is a critical examination of settler-colonial nostalgia in the Flinders Ranges, within an artistic context. The project is underpinned by a partnership with the State Library of South Australia (SLSA) and the Adnyamathanha Traditional Lands Association, and it was exhibited at the SLSA in Adelaide, March–May 2017. Spread across the SLSA Institute Gallery, on the videowall in the Spence Walkway, and on the Storywall outdoor architectural projection, the exhibition consists of a range of photographic and video art works alongside portrait images of Adnyamathanha people taken in 1937 at the Nepabunna Mission by Charles Mountford, and video interviews with descendants of the people in the portraits. In this article, we discuss the components of the exhibition and its artistic and curatorial rationale and, in so doing, propose a series of responses to the key question that guided our activities on this project: What strategies and practices can non-Aboriginal artists employ to question the dominance of settler-colonial nostalgia in Australia?